The influence stakeholders in the process of innovation activity enterprises - Liezina, A. (Baltic International Academy, 2019)
У дослідженні розглядається актуальна проблема взаємодії стейкхолдерів та інноваційних процесів підприємства, яка, на думку автора, являє собою взаємопов’язану систему безперервної дії. Представлено авторське бачення кроків, які можуть допомогти в процесі впровадження інновацій у діяльність підприємства, а також груп зацікавлених сторін, яким необхідно скласти карту зацікавлених сторін для досягнення максимального ефекту. The study examines the current problem of interaction between stakeholders and innovation processes of the enterprise, which, according to the author, is an interconnected system of continuous action. The author's vision of the steps that can help in the process of implementing innovations in the enterprise, as well as stakeholder groups who need to draw up a map of stakeholders to achieve maximum effect.
Keywords: стейкхолдери; enterprise; innovations; stakeholders